MAINTAINING THE NEUTRALITY OF THE STATE CIVIL APPARATUS IN POLITICAL CONTESTATION IN INDONESIA - Harahap, Raegen; Sitorus, Triana Putri; Alkadafi, Muammar (Jurnal EL-RIYASAH, 2024)
This study explores the impact of Joint Decree (SKB) 3 Ministers 2022 on the neutrality of State Civil Apparatus (ASN) during social events, specifically weddings, amidst the political climate of the 2024 Indonesian elections. The findings reveal that SKB 3 Menteri has heightened awareness among ASN regarding the importance of maintaining a non-partisan stance, even in personal celebrations. The study identifies subtle behavioural shifts, such as avoidance of hand gestures or poses that could be perceived as political endorsements, demonstrating compliance with the directive. However, this heightened caution also created a palpable sense of restraint among wedding participants, leading to a more formal and less expressive atmosphere. The implications suggest that while SKB 3 Menteri has effectively curbed overt political signalling, it also highlights the complexities of enforcing neutrality in social contexts. Policymakers are encouraged to balance strict enforcement with clearer guidelines to avoid excessive restrictions on personal expressions while upholding the integrity of democratic processes.